DISPARITY IN AUTHORITY AND EFFECTIVENESS OF OMBUDSMAN’S RECOMMENDATIONS IN PREVENTING MALADMINISTRATION - Sulistyowati, Sulistyowati; Maharani, Dewi Nadya; Maharaja, Gusti Bintang (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2025)
Ombudsman of the Republic of Indonesia (ORI) oversees public services and prevents maladministration, yet its recommendations, despite a strong legal basis, are often treated as non-binding, resulting in persistent non-compliance. This study aims to assess the effectiveness of the Ombudsman’s authority in preventing maladministration and to propose normative and institutional measures to enhance bureaucratic compliance. The research employs a normative legal methodology, focusing on the analysis of key regulatory frameworks, particularly Law No. 25 of 2009 on Public Services and Law No. 37 of 2008 on the Ombudsman of the Republic of Indonesia. Data were collected through a comprehensive literature review and analyzed using descriptive-analytical techniques. The findings reveal that weak compliance with Ombudsman recommendations is primarily driven by bureaucratic resistance, political interference, and institutional capacity constraints. The novelty of this study lies in its argument for strengthening the Ombudsman through legislative reform, including the introduction of limited executive authority, enhanced institutional autonomy, and proactive supervisory mechanisms. The study concludes that reinforcing the legal and institutional position of the Ombudsman is essential not only to improve administrative accountability but also to reflect the state’s genuine commitment to the rule of law, democratic governance, and effective public service delivery.